Natural language processing for structuring clinical text data on depression using UK-CRIS - Vaci, N; Liu, Q; Kormilitzin, A; De Crescenzo, F; Kurtulmus, A; Harvey, J; O'Dell, B; Innocent, S; Tomlinson, A; Cipriani, A; Nevado-Holgado, A (BMJ Publishing Group, 2020)
Background Utilisation of routinely collected electronic health records from secondary care offers unprecedented possibilities for medical science research but can also present difficulties. One key issue is that medical information is presented as free-form text and, therefore, requires time commitment from clinicians to manually extract salient information. Natural language processing (NLP) methods can be used to automatically extract clinically relevant information.